1984
DOI: 10.1007/bf01129622
|View full text |Cite
|
Sign up to set email alerts
|

Human in vitro fertilization employing individualized ovulation induction by human menopausal gonadotropins

Abstract: One hundred six women suffering from obstructive tubal disease not corrected by previous surgery were treated in an in vitro fertilization (IVF) program. Ovulation was induced by 3 amps of human menopausal gonadotropin (HMG)/day starting on the third day of the cycle for 5 days. In most of the patients the regimen was continued for another 1-3 days, depending on the individual's ovarian response (mean, 20 +/- 5 amps/cycle). Monitoring consisted of daily follicular ultrasonography and serum estradiol measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…17,27 Nevertheless, in our program, only 4 out of 123 women were found to have inaccessible ovaries due to adhesions. 21 Therefore, we do not feel that it is justifiable to perform a screening laparoscopy, and in this we are in agreement with Wentz and colleagues 28 and Kerin and colleagues. 29 On the other hand, in patients undergoing repeat reconstructive surgery, we perform an ovarian suspension, preparing them for eventual IVF, by fixing the ovaries to the anterior lateral surface of the uterus, with very satisfactory results.…”
Section: Tubal Factorsupporting
confidence: 66%
See 2 more Smart Citations
“…17,27 Nevertheless, in our program, only 4 out of 123 women were found to have inaccessible ovaries due to adhesions. 21 Therefore, we do not feel that it is justifiable to perform a screening laparoscopy, and in this we are in agreement with Wentz and colleagues 28 and Kerin and colleagues. 29 On the other hand, in patients undergoing repeat reconstructive surgery, we perform an ovarian suspension, preparing them for eventual IVF, by fixing the ovaries to the anterior lateral surface of the uterus, with very satisfactory results.…”
Section: Tubal Factorsupporting
confidence: 66%
“…All patients enrolled in an IVF program must have a normal uterus, functioning ovaries, and, according to most studies, should be under 35 to 40 years old. 15 " 21 This age limit, however, should probably be re-evaluated, since it was recently shown that up to the age of 44, neither fertilization nor pregnancy rates are significantly affected. 22…”
Section: Selection Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Netherlands), according to a previously described protocol [12]. Oocytes were aspirated by laparoscopy, and 6 h later semen specimens were obtained from their male partners by masturbation following 3-5 days of sexual abstinence.…”
Section: Methodsmentioning
confidence: 99%
“…In IVF programmes, where multiple follicular development is stimulated with clomiphene alone, human menopausal gonadotrophin (hMG) alone, or clomiphene plus hMG, human chorionic gonadotrophin (hCG) is usually given when the leading follicle is 5 18 mm in diameter (Edwards 1981;Buttery ef al. 1983;Garcia et al 1983;Laufer et al 1984). The natural history of such follicles without hCG has not been well described and indeed there is some continuing dispute as to whether an endogenous L H surge will occur spontaneously in hMG stimulated cycles (Ferraretti et al 1983).…”
mentioning
confidence: 99%